Modeling the Impact of Soil Porosity on Nitrate Leaching to Groundwater Using the Advection Dispersion Equation - Ochwach, Jimrise O.; Okongo, Mark O.; Musundi, Sammy W. (OSR journal, 2018)
Abstract Nitrogen is a vital nutrient that enhances plant growth which has motivated the intensive use of nitrogen-based fertilizers to boost crop productivity. However, Pollution by nitrate is a globally growing problem due to the population growth, increase in the demand for food and inappropriate Nitrogen application. The complexities and challenges in quantifying nitrate leaching have led to development of a range of measurement and modeling techniques. However, most of them are not widely applied due to their inaccuracy. This calls for new approaches in which nitrate leaching can be analysed in order to give better understanding of nitrate fate and transport process for proper management of groundwater. This s t u d y has developed a mathematical model to analyse n i t r a t e leaching into groundwater from the advection-dispersion equation. The advectiondispersion equation is modified by incorporating soil porosity and transformed to a second order ordinary differential equation by Laplace and solved. Simulations showing the variation of soil porosity is presented using the MATLAB software. The study has shown that nitrate leaching to groundwater is directly proportional to soil porosity such that more porous soil will allow more nitrate to reach to the groundwater within a short time leading to faster contamination of groundwater. The results is useful to farmers, policy makers, researchers and the general public for the purpose of understanding movement of nitrates through the soil and also provide science-based input into best alternative mathematical model which can be used to analyse leaching of nitrate into groundwater
Keywords: Nitrate; Modeling; Advection-Dispersion; Leaching; Gro u n d wa t e r; Soil Porosit